2019
DOI: 10.1590/0104-1428.05019
|View full text |Cite
|
Sign up to set email alerts
|

Influences of the mesh in the CAE simulation for plastic injection molding

Abstract: Although computer-aided engineering (CAE) software has been used for many years in the plastic industry, identifying the most appropriate mesh geometry and density remains a challenge. It can affect the accuracy of the simulation, the time and the costs. The evaluation of the most suitable mesh is not easy because the difficulties to obtain the real the values of the pressure and temperature inside the mold. The current work investigates this issue. A mold was manufactured and sensors were installed in its int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…Te mesh size is one of the factors contributing to the convergence criteria. It has been also reported that mesh fneness and coarseness have a signifcant efect on computation time [58,[63][64][65][66]. Te guideline for maximum mesh size was already stated in the previous report [58,67].…”
Section: Finite Element Modeling Of Encased Composite Columnmentioning
confidence: 87%
“…Te mesh size is one of the factors contributing to the convergence criteria. It has been also reported that mesh fneness and coarseness have a signifcant efect on computation time [58,[63][64][65][66]. Te guideline for maximum mesh size was already stated in the previous report [58,67].…”
Section: Finite Element Modeling Of Encased Composite Columnmentioning
confidence: 87%
“…Miranda and Nogueira [36] experimentally compared the influence of the mesh size in relation to actual injected components, who indicated little variation in the simulated results for mesh sizes smaller than 1.25 mm. Marin et al [37] compared the effect of mesh density in the injection pressure, reaching highest precision in a dual-domain mesh with sizes between 2.0 and 4.0 mm. It is worthy to note that the aforementioned mesh sizes are associated with the part or product sizes and shape, especially thickness variations and the presence of free-form shapes.…”
Section: Convergence Analysismentioning
confidence: 99%
“…Today, numerical simulations by computer‐aided engineering software (CAE) are the most used tool to simulate this injection molding process. The investigation presented by Marin et al [ 4 ] demonstrated that current CAE software can achieve high accuracy for predicting temperature and pressure inside mold cavities during injection processes (98% and 97%, respectively), but it takes into account the process dynamics only within one injection cycle. Thus, transient regimes due to thermal perturbations or variations in the polymer properties cannot be predicted by CAE approaches.…”
Section: Introductionmentioning
confidence: 99%